Palitya w.s.r to Premature Graying of Hair -An Ayurvedic Overview (AYUSHDHARA, 2022)
Premature graying of hair is referred to as "Palitya" in the Ayurvedic method and falls under the general category of "Shiroroga."Palitya mainly shows Dosha’s imbalance of our body. This premature graying of hair refers to the graying of hair in young age or before the age of 35 years. In Ayurveda this is known as “Palitya”. Grey Hair is caused by gradual reduction of melanin production overtime in your hair follicles. Melanin a pigment that gives colour and smoothness to your hair. Eventually the hair begins to lose its colour. Ayurveda says, the “Bhrajaka Pitta a pigment responsible for imparting natural colour to our skin as well as to hair also seated in superficial layer of skin (Avabhasini). Soft, lustrous, silky, black hair are the sign of long healthy life span as per said by Acharya Charaka. In the present era sedentary life style, imbalanced diet, tense, mental conditions and polluted hair, water and food have led to lot of complications which are difficult to remove. Therefore global interest these days is developing towards Ayurveda to face the Challenge be it preventive aspect or curative treatment method of pacification, management of disease in its initial stage or final stage. To gather all information related to Palitya at one place which is availed in different Ayurvedic texts and for elucidation of this knowledge in a proper manner the present study has been undertaken.